Harnessing Visual Media for EFL Learning: Benefits, Challenges, and Pedagogical Strategies - Rum, Eka Prabawati; Baso, Farisha Andi; Girik Allo, Markus Deli; Musoyeva, Aziza (Universitas Sulawesi Barat, 2026)
In English as a Foreign Language (EFL) teaching, the advent of visual media has profoundly impacted education by offering fresh opportunities to motivate learners and explain intricate linguistic ideas. The current research investigated the perceptions of EFL learners at the university level regarding the advantages and disadvantages posed by visual media. A qualitative case study design was employed to gather data through open-ended questionnaires distributed to five purposefully selected students, aiming to capture the full range of a multimedia-informed continuum of proficiency and prior exposure. Thematic analysis revealed three primary themes: (a) visual media significantly enhances engagement and understanding, contributing to more interactive lessons and appreciation of abstract language components; (b) significant challenges like insufficient broadband access, overly complex content far exceeding students’ capabilities, lessons dominated by the need to pre-analyze visuals at the expense of text, and lack of access to certain media presented barriers; and (c) students recommended practical strategies for optimizing visual media use, such as aligning content with cultural and linguistic contexts, incorporating interactive teaching methods, providing offline resources, and enhancing teacher training in multimedia integration. This insight extends the literature, evidencing the simultaneous promise and challenge interactions posed for language learning through visual media. This study enhances the understanding of the impact of media on the efficient utilization of EFL instruction within the frameworks of discourse and paradigms, including balance, context-appropriate use, pathways into the study of sustained and new technological impacts, and multilayered inquiry for technology’s influence over time.